Soul Catcher - White, Michael (London Quercus, 2007)
In the tradition of Cold Mountain comes this bold, exquisitely written and profoundly moving epic of a slave catcher and a young woman on the run on the eve of the Civil War
Keywords: Fugitive slaves -- Slavery -- Southern States